The bottomonium spectrum at finite temperature from N f = 2 + 1 lattice QCD - RYAN, SINEAD (My University, 2014)
We present results on the bottomonium spectrum at temperatures above and below the deconfinement crossover temperature, T c , from dynamical lattice QCD simu- lations. The heavy quark is treated with a non-relativistic effective field theory on the lattice and serves as a probe of the hot medium. Ensembles with a finer spatial lattice spacing and a greater range of temperatures below T c than those previously employed by this collaboration are used. In addition, there are N f = 2 + 1 flavours of Wilson clover quark in the sea with M π ≈ 400 MeV and we perform a more careful tuning of the bottom quark mass in this work. We calculate the spectral functions of S and P wave bottomonium states using the maximum entropy method and confirm earlier findings on the survival of the ground state S wave states up to at least 2 T c and the immediate dissociation of the P wave states above T c
PUBLISHED
Keywords: bottomonium spectrum at temperatures; bottomonium spectrum at temperatures